The Essence of Halal Ecosystem in Pesantren Business in Optimizing Toward Sustainable Economy - Shinta Retnowati, May; Sukoco, Daud; Fitiyani, Mufti (KnE Social Sciences, 2024)
In the era of globalization, the halal product market has grown to become a significant contributor to the global economy. Pesantren is the ideal place for the implementation of the halal system. This is also supported by the territory of Indonesia, which is a majority Muslim community, so that Halal is not only an important aspect of Islamic teachings but also a necessity. One of the most important halal needs is to pay attention to food and beverages. The halal sector promotes the idea of goodness for consumption as a guarantee of the highest quality of goods and services. The purpose of industrial economics is to explain the ways of development in the economic sector, for the halal industry in Pesantren to have an economic impact on Pesantren and the surrounding community. The research method uses qualitative with a descriptive inductive approach. The study results show that business units in Islamic boarding schools, such as Roya always maintain the quantity and quality of halal both from products, systems, services, and human resources so as to optimize halal value impacting sustainable economy. The sustainable impact can be felt directly by the big family of the Pesantren, and also the Pesantren workers taken from the community around the cottage in order to feel the blessing of halal cycle. Keywords: business unit of Pesantren, halal industry, halal, products